Climate influence on rockfalls in high-Alpine steep rockwalls: The north side of the Aiguilles de Chamonix (Mont Blanc massif) since the end of the 'Little Ice Age' - Ravanel, Ludovic; Deline, Philip (The Holocene, 2010)
International audience Rockfalls fundamentally affect the morphodynamics of high mountain rockwalls, and represent a great danger for both people and infrastructures, but still are poorly known. By comparing old, recent and new photographs, in addition to geomorphological field data, we propose an inventory of the rockfalls that occurred since the end of the 'Little Ice Age' on the north side of the Aiguilles de Chamonix (Mont Blanc massif), ranging in volume from 500 to 65 000 m3. These 42 rockfalls occurred after 1947, of which > 70% during the last two decades, with a maximal frequency during the warm summers, especially in 2003. Average elevation of scars (3130 m a.s.l.) close to the lower modelled permafrost limit, and the topography (e.g. spurs) of the affected rock faces enhancing lateral heat fluxes, suggest that a climatically driven permafrost degradation has triggered many of the recent rockfalls in high-Alpine steep rockwalls.